The Influence of Parenting Styles of Working and Non-Working Mothers on Children’s Independence - Supriatin; Andi Halimah; Yudistira; Sri Saadiyah Leksonowati; Tiar Erawan (Jurnal Penelitian Pendidikan IPA, 2024)
The purpose of this study was to determine the effect of parenting styles of working and non-working mothers on children's independence. This study is a quantitative study using SPPS version 27. The population consists of two categories, namely working mothers and non-working mothers in Lette Village, Marsio District, South Sulawesi. The sample in this study was 135. The analysis used was multiple linear analysis. The results showed that the parenting of working mothers had a positive and significant effect on children's independence as evidenced by the results of the T-test of 4.87> 1.97 and a p-value of 0.00 <0.05. Parenting patterns of non-working mothers do not have a positive and significant partial effect on children's independence from the results of the T-count -7.88 < 1.97 T-table and p-value 0.00 < 0.05. Parenting of working mothers and parenting of non-working mothers simultaneously have a positive and significant effect on the dependent variable of child independence with the results of F-count 53.84> F-table 3.07 and 0.00 <0.05. Based on the results of the research, it can be concluded that there is a positive and significant effect simultaneously on the parenting style of working and non-working mothers on children's independence.